Integrated assessment of oil leaking accident site with long-term artificial interference. Issue 2 (14th January 2019) - Liu, Fuming; Yi, Shuping; Zheng, Wentang; Ma, Hongyun; Qin, Jianbo; Huang, Junyi
Abstract : This paper provides a case study of an assessment of an oil leaking accident site after long-term artificial interference. A cost-effective, rapid and quantitative assessment was carried out in the following order: site hydrogeology study, joint on-site geophysical prospecting (high-density electrical method and ground-penetrating radar method), borehole investigation, sample testing and integrated assessment. The results indicate that oil plumes have been transported from the leak spot to the downstream area, suggesting that surface artificial rainfall is helpful in driving the crude oil plumes. Aquifer heterogeneity dominates the behaviours of the plume movement at site scale. Two residual oil plumes were confirmed, with an estimated total volume of 325·6 m 3 for the contaminated soil and groundwater. At last, a site-specific joint leaching, pumping and treating method is proposed for the clean-up of the residual crude oil. This study is provided for a precise assessment prior to remediation.